A use case of exclusive economic zone of Pakistan for wave power potential estimation. (1st October 2021) - Khan, Madeeha; Khalid, Azfar; Lughmani, Waqas Akbar; Khan, Muhammad Mahabat
Abstract: The demand for energy is constantly rising in developing countries. Ocean waves with continuous energy flux can contribute to universal energy production. The wave energy has its advantages of renewable, non-polluting and large storage, however, the technological solution to extract energy from oceans is still at early stages. In this paper, a strategy is devised to estimate wave power potential for a developing country. Pakistan is considered as a use case on the basis of less renewable energy share and facing energy crises. In this study, wave energy potential is estimated for power generation by excluding the sensitive areas from the exclusive economic zone. The year long significant wave height and mean wave period data set is used for the purpose. A GIS based multi-criteria overlay analysis model is implemented using different restriction and weighted factors such as ocean bathymetry, distance to ports and shoreline. The results show that average wave power is peaked at 9.15 kW/m in the summer season and 85% of Pakistan economic zone is suitable for wave farm development. The wave energy potential assessment is coupled by extractable power estimation that is worked out by assessing the performance of commercial wave energy converters in regional context. Highlights: A strategy to estimate wave power potential of a marine economic zone is devised. Potential area is estimated by sensitive area subtraction using GIS and overlay analysis. Temporal variations and the annual average wave energy potential is quantified. Power pattern knowledge is transformed for WEC power plants development. Commercial wave energy converters are compared for performance efficiency in regional sea conditions.